Dualistic influences of Pr3+ ions on the optical and radiation shielding characteristics of alumina bismuth – Sodium phosphate glasses. (June 2023) - Saddeek, Yasser B.; Aly, K.A.; Showahy, A.A.; Elsaman, Reda
Abstract: Using a standard melt quenching technique, alumina bismuth-sodium phosphate glasses doped with Pr2 O3 were synthesized. The amorphous character of these glasses was confirmed by the XRD spectrum. The impact of Pr2 O3 on optical and radiation-shielding characteristics has also been studied and linked to the structure. The optical characteristics show a decrement of the optical band gap from 3.72 to 3.48 eV, and an increment of the refractive index along with a clear red shift with the addition of Pr2 O3 content. The refractive index of Pr2 O3 -based glasses was estimated with the help of the glass electronegativity (Δχ) and Eg values. The increment of Pr2 O3 increases the mass attenuation coefficient (MAC) values and decreases the half-value layer (HVL) values, which improves the shielding ability of the manufactured glasses. The strongest interactions between photons and glass atoms occurred at about 100 keV, which causes the glass samples to exhibit remarkable photon-blocking characteristics, according to the effective atomic number (Zeff ) data. The radiation shielding variables led to the finding that glass containing 2 mol% Pr2 O3 provides better results among the samples that were synthesized. Highlights: Al2 O3 –Na2 O–Bi2 O3 –P2 O5 glass matrices doped with Pr2 O3 were developed. Experimental optical and radiation shielding parameters are studied. The theoretical values of radiation shielding parameters were calculated. Samples in this work present better response than some heavyweight concrete mixes.